Motivating first-year engineering students through gamified homework. Issue 5 (20th October 2021) - Kulhanek, Abigail; Butler, Brittany; Bodnar, Cheryl A.
ABSTRACT: Gamification has been applied in multiple different contexts for increasing motivation towards completion of activities such as company loyalty programs, exercise initiatives, and corporate training. Although gamification has been applied within engineering classrooms previously, very little results have been obtained on how gamification approaches can impact student academic motivation. This study applied an action research approach to the development of curricular content for an online gamification platform that could be used for homework in a first-year second semester engineering design course. During the two cycles performed, researchers learned from the students directly what elements of the platform appealed to them and helped with their learning process allowing the researchers to make active changes to the gamification platform throughout the semester as well as in between cycles to improve final outcomes. After completion of the second cycle of analysis, the researchers were able to create content for a gamification platform that has been shown to be able to empower students towards learning engineering material while providing them with the necessary support so that they can feel successful although further refinement based on student comments and feedback is still necessary. Students also felt that the content built into the platform was of interest to them and useful to their overall learning process. This study demonstrated the utility of using action research as a means to actively incorporate student feedback in the development of educational innovations leading to ongoing improvements and a final product that meets the intended needs of its target population.